Homeopathy in healthcare -- effectiveness, appropriateness, safety, costs an HTA report on homeopathy as part of the Swiss Complementary Medicine Evaluation Programme - Bornhöft, Gudrun; Matthiessen, Peter F.; SpringerLink (Online service). (Berlin Springer, 2011)
This volume includes the full Health Technology Assessment (HTA) report on effectiveness, appropriateness, safety and costs of homoeopathy in health care. The report was commissioned by the Swiss health authorities to inform decision-making on the further inclusion of homoeopathy in the list of services covered by statutory health insurance. Other studies carried out as part of the Swiss Complementary Medicine Evaluation Programme (PEK) caused a massive stir due to their schematic and exclusively quantitative (negative-)outcomes for homoeopathy. The present report, in contrast, offers a differentiated evaluation of the practice of homoeopathy in health care. It confirms homoeopathy as a valuable addition to the conventional medical landscape ? a status it has been holding for a long time in practical health care.
Introduction -- Background and objectives of HTA -- Introduction to the speciality of homeopathy - principles and definition -- Homeopathy: Research and Research Problems (preclinical and clinical) -- General problems with clinical trials in research -- HTA Homeopathy: Methods and Material -- International Utilisation of Complementary Medical Approaches -- CAM Conditions and Use in Switzerland -- Overview of Systematic Reviews on the Clinical Efficacy of Homeopathy -- Clinical Studies on the Effectiveness of Homeopathy for URTI/A (Upper Respiratory Tract Infections and Allergic Reactions) -- Safety of Homeopathic Use -- Cost-effectiveness of Homeopathy -- Full discussion of the HTA results -- Synopsis.
Electronic reproduction.
Keywords: Homeopathy -- Switzerland; Homeopathy -- Research; Electronic books